Bio-based poly(benzimidazole--amide)-derived N, O co-doped carbons as fast-charging anodes for lithium-ion batteries - Patnaik, Kottisa Sumala; Mantripragada, Bharat Srimitra; Badam, Rajashekar; Higashimine, Koichi; Zhong, Xianzhu; Kaneko, Tatsuo; Matsumi, Noriyoshi (Nanoscale advances, 2024)
Lithium-ion batteries (LIBs) that can be charged faster while delivering high capacity are currently in significant demand, especially for electric vehicle applications. In this context, this study introduces a less-explored subject: nitrogen and oxygen dual-doped carbons derived from bio-based copolymers, specifically poly(benzimidazole- co -amide). The synthesis involved varying proportions of benzimidazole to amide, namely, 8.5 : 1.5, 7 : 3, and 5 : 5. The copolymers were pyrolyzed under a nitrogen atmosphere to obtain co-doped carbons, wherein the copolymers acted as single sources of carbon, nitrogen, and oxygen, with the nitrogen content ranging between 12.1 and 8.0 at% and oxygen doping between 11.8 and 25.0 at%, and were named as pyrolyzed polybenzimidazole- co -amide 8.5-1.5, 7-3, and 5-5. Coin cells were fabricated and rate studies were conducted for all three samples, wherein PYPBIPA8.5-1.5 outperformed all others, especially at higher current densities. Intrigued by these interesting results, when long-cycling studies were performed at a high current density of 4.0 A g −1 , pyrolysed polybenzimidazole- co -amide 8.5-1.5 showed a delithiation capacity of 135 mA h g −1 compared to pyrolysed polybenzimidazole- co -amide 7-3 and 5-5 with a delithiation capacity of 100 mA h g −1 and 60 mA h g −1 , respectively, with a capacity retention of 90% even after 3000 cycles. Furthermore, a full cell (2025-coin cell) was fabricated using the PYPBIPA8.5-1.5 anode and LiNi 0.80 Co 0.15 Al 0.05 O 2 (LiNCAO) cathode. This works presents a nitrogen and oxygen co-doped carbon obtained from a bio-based polymer as anode active material for fast charging in lithium-ion batteries.